Pre-Service English Language Teachers' Levels of Reflectivity during the Process of Identity Construction in Pedagogical Practicum: A Snowball? - Angélica María Pita-Castro; Yury Alicia Castiblanco-Rincón (Asociación Colombiana de Profesores de Ingles, 2021)
This research study is about the way pre-service English language teachers' levels of reflectivity, proposed by Van Manen, give an account of the construction of their identity as language teachers during their pedagogical practicum in a BA program of English Language Teaching at a private university in Bogota, Colombia. This study follows the principles of narrative research to explore the way the participants live their pedagogical practicum experience. Data were collected from the participants' reflective journals and audio-recorded semi-structured interviews. Findings reveal that pre-service English language teachers possess a level of reflectivity, although they are unaware of it at the beginning of their pedagogical practicum. Thus, their identities as language teachers are constructed depending on the context, the people that are around them, and the specific time; hence, the levels of reflectivity as proposed by Van Manen are set in an incognito manner.